PERLINDUNGAN HUKUM TERHADAP PENGEMUDI TRANSPORTASI ONLINE PEREMPUAN BERDASARKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Elda Mitari; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Labor has a very important role in national development. These resources interact with other development capital, coupled with the role of technology will support development programs in the field of economy and community welfare. Legal protection is all effort made consciously by every person or government or private institution that aims to seek security, control and fulfillment of welfare in accordance with human rights. At the beginning of its emergence, it was started by the Uber application that carries Uber Taxi as an online application-based transportation service business. Then followed by the appearance of GOJEK, GrabBike, GrabTaxi, and other online-based applications. Facing technological advances should be accompanied by labor law reforms. Because in carrying out their work there are threats and dangers that can occur to women online transportation drivers, but there are no specific arrangements related to legal protection for drivers of online transportation. In the city of Pekanbaru, it has developed with the presence of online drivers who use internet applications.The problems that are the object of this research are: First, What is the regulation of legal protection for female online transportation drivers based on the legislation in Indonesia? Secondly, Are legal arrangements related to online transportation drivers providing legal protection for female online transportation drivers ??This type of research is Normative legal research.The results of this study are First, There are no specific arrangements related to Legal Protection of Women Online Transportation Drivers. Because the relationship between service providers and drivers Online transportation is a partner, not an employment relationship as referred to in Law Number 13 of 2003 concerning Manpower. So that work protection against drivers Women's online transportation cannot be based on work protection for women referred to in Law Number 13 of 2003. Secondly, with the absence of an arrangement that becomes the legal basis for Legal Protection for Female Online Transportation Drivers, meaning that there is no Legal Protection For Women Online Transportation Drivers. This is because the partnership relationship applies, a legal reform is needed in Indonesia regarding the Regulation of Legal Protection for Women Online Transportation Drivers.